Manufactured uncertainty : implications for climate change skepticism - Code, Lorraine (Albany : State University of New York Press, 2020)
"Wide-ranging critique of the epistemological and ethical assumptions that underlie contemporary debates concerning climate change"--
Intro -- Contents -- Foreword -- Acknowledgments -- Introduction -- Chapter 1 Epistemic Responsibility, Now -- The Myth of "The Individual" -- Culpable Ignorance? -- Chapter 2 Doubt and Denial: Epistemic Responsibility Meets Climate Change Skepticism -- "Manufactured Uncertainty"-Merchants of Doubt -- Epistemic Identity and Situation -- Chapter 3 Care, Concern, and Advocacy: Is There a Place for Epistemic Responsibility? -- Very Vulnerable Bodies -- Advocacy and/or Objectivity? -- Conclusion: Knowledge as Collective/Collaborative Practice -- Chapter 4 Particularity, Epistemic Responsibility, and the Ecological Imaginary -- Epistemology and the Social Imaginary -- Chapter 5 How to Think Globally, Revisited: Or, A Plea for Ignorance -- Hermeneutic Humility -- Strategic Ignorance -- Intellectual Virtue -- Epistemic Responsibility and Virtuous Knowing Today -- Bibliography -- Index.
JSTOR
Keywords: Climatic changes -- Philosophy; Environmental responsibility; Knowledge, Sociology of; Climat -- Changements -- Philosophie; Responsabilité environnementale; Sociologie de la connaissance; sociology of knowledge; Environmental responsibility; Knowledge, Sociology of